The rice observatory: A digital showcase for research & data to enable the rice sector improvement - Andrade, R.; Rivera, T.; Hoyos, N.; Vergara, D.; Nasner, H. (2023)
Globally, there has been an explosion of data generation in agriculture. With such a deluge of data available, it has become essential to create solutions that organize, analyze, and visualize it to gain actionable insights, which can guide farmers, scientists, or policy makers to take better decisions that lead to transformative actions for agriculture. Crop Observatories Alliance are presented as an initiative that aims to harmonize large amounts of crop-specific data from various open access sources to build relevant indicators for decision making and showcasing our own information.